Surgical outcomes of a low-cost adapted sacrospinous fixation for apical prolapse repair - Francilberto Souza; Artur Eduardo de Oliveira Rangel; Alex Sandro Rolland Souza; Aurélio Antônio Ribeiro Costa (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To assess surgical outcomes of women submitted to the adapted sacrospinous fixation (SSF) at a school hospital in northeastern Brazil for apical prolapse repair. Methods: Retrospective study with medical records of women submitted to the adapted SSF at a reference center in Brazil (2015 to 2019). All women submitted to this SSF were included, and those with pelvic organ prolapse (POP) recurrence, repair using other techniques, or unavailable medical records were excluded. The anatomical result, surgical characteristics, and associated complications and recurrence were evaluated. The chi-square and Fisher's exact test were used for statistical analysis, using a significance level of 5%. Results: A total of 198 medical records were included. The mean age was 65.1 ± 8.2 years; most had less than eight years of education, were menopausal, multiparous, and with urinary incontinence. The postoperative POP stage significantly improved at all compartments. The complication rate was 15.7%, especially due to de novo urinary incontinence (n = 12; 6%). Five cases of mesh-related complications (5%) were observed. The median follow-up was nine months, with 8.4% of POP recurrence and reoperation. POP recurrence or mesh-related complications were not associated with sociodemographic, clinical, or surgical characteristics.[...]